The culture of tolerance in families of new muslims convert - Suraya Sintang; Khadijah Mohd Khambali; Nurhanisah Senin; Suhaida Shahrud-Din; Nur Farhana Abdul Rahman; Siti Hamimah Mat Zin (IDOSI Publications, 2013)
In this paper, the authors seek to highlight the importance of tolerance in the pluralistic community of Malaysia as being stated in Article 11 of the constitution which stresses religious freedom in developing a harmonious co-existence. To recognize the tolerance practices in Malaysia, this paper focuses on the new converts in Sabah. As this is a qualitative research in nature, it includes in-depth interviews with the new Sabahan Muslim converts comprised of Kadazandusun, Murut, Rungus, Sino and Chinese. The questions that arise basically pertainto their relationship with their family of previous faith after they have converted to Islam. The results confirm that living in a multi-faith surroundingis not a forbidding factor in developing religious and cultural tolerance amongst the family members. The daily communication and accommodation even develop better mutual understanding, respect and tolerance towards the new Muslim that eventually leads to the supportive response from the family of origin in practising the new lifestyle as a Muslim. In sum, the cultural tolerance has superseded the diversity of religions and ethnics in Malaysia through extensive daily communications and encounters amongst the different faith societies